Fabrication and characterization of Al/Ta thin films as metal junctions for solar cell applications - Singh, Parmar, Avanish (Elsevier B.V., 2023)
In the present work, the effect of deposition time (10 min, 20 min, and 30 min) on the structural, morphological, and electrical properties of Al/Ta thin films has been investigated. The XRD and microscopy results revealed that the thin films exhibit a bcc structure, with a strong (1 1 0) preferred orientation and followed a columnar growth with grain sizes lower than 100 nm. Thin film with 20-min deposition time exhibits less average roughness and better morphology than 10-min and 30-min. Further, the average resistance was smallest for thin films with 20-min of deposition time along with the optical reflectance between 50 and 85% in wavelength region of 400–1000 nm. The Al/Ta thin film can be employed as an excellent back-contact material for thinfilm solar cells due to its improved crystallinity, reflectance, and lower resistivity. © 2022 The Authors
Keywords: Direct current magnetron sputtering; Metal junction; Sheet resistance; Ta/Al thin film